Forage Grass Tolerance to Pasture Herbicides - Brent A. Sellers; Jason A. Ferrell (EDIS, 2010)
Revised! SS-AGR-87, a 2-page illustrated fact sheet by Brent A. Sellers and Jason A. Ferrell, describes the tolerance of forage cultivars grown in Florida to herbicides currently registered for use in pastures. Published by the UF Department of Agronomy, May 2010.